The Mixed Oxide in Bi2O3-ZnO-CeO2 System Prepared by Solid State Reaction - Těšitelová, Kateřina; Šulcová, Petra (Česká společnost průmyslové chemie, 2017)
The prepared samples with composion Bi1.5Zn0.5Ce2O7 were characterized by X-ray diffraction analysis. XRD analysis indicates that mixed oxide pigments are multiphase. Studied powder materials with defect structure of CeO2 are characterized by dark yellow and yellow-orange hues, depending on the calcination temperature.
Směsný oxid na bázi Bi2O3-ZnO-CeO2 připravený reakcí v pevné fázi
Keywords: Mixed oxide pigment; Inorganic pigment; Bi2O3-ZnO-CeO2 system; Colour properties; směsný oxidický pigment; anorganický pigment; Bi2O3-ZnO-CeO2 systém; barevné vlastnosti